API PENYUCIAN DALAM PENGAJARAN GEREJA KATOLIK ST. YOSEPH PALEMBANG - Indahsari, Ade Destarahayu; Fitriyana, Nur; Hayati, Sofia (Jurnal Studi Agama, 2021)
Purgatory is a process for those who die unfriendly to God. Therefore, we have to go through purgatory to ascend to heaven. Purgatory is typical teaching of the Catholic Church that is traditionally passed on and maintained by Catholics. To pray for the souls whose souls are in purgatory through the celebration of the Eucharist. Although purgatory is not a liturgical practice, it has a rite. Every November 2nd is celebrated as the Day of the Souls. The Bible does not say about this. But 2 Maccabees 12: 38-45 is considered relevant to this tradition. This teaching was emphasized at the Second Council of Lyon (1274), the Council of Ferrara-Firenza (1439), and the Council of Trent. This type of research is field research. The data sources in this study are primary data and secondary data. Primary data were obtained directly from pastors at St Yoseph Church, Palembang. Meanwhile, secondary data is in the form of books, scientific papers, and documents related to research. Data collection techniques by observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The results of this study indicate that purgatory is dogmatic teaching or concept of faith, not a liturgical practice or worship. The implementation of the purgatory rite at St. Yosepeh Church, Palembang, began with intention and devotion at the Eucharistic celebration. Then proceed with four stages, namely the opening rite, the liturgy of the word, the eucharistic liturgy, and the closing rite.